Analysis of QRIS Payment Accessibility and Perceived Benefits as Determinants of Financial Performance for Culinary SMEs in Tangerang - Muhammad Faisal; Rival Pahrijal; Muhamad Ammar Muhtadi (West Science Social and Humanities Studies, 2026)
This study analyzes the influence of QRIS payment accessibility and perceived benefits on the financial performance of culinary SMEs in Tangerang. The increasing adoption of digital payment systems, particularly QRIS introduced by Bank Indonesia, has transformed transaction processes and business operations among SMEs. However, the extent to which accessibility and perceived benefits contribute to financial performance remains an empirical question. This research employs a quantitative approach using primary data collected from 185 culinary SME owners through structured questionnaires measured on a Likert scale. Data analysis was conducted using IBM SPSS Statistics 25, including descriptive statistics, validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that QRIS payment accessibility has a positive and significant effect on financial performance, suggesting that ease of use and availability of digital payment systems enhance transaction efficiency and business operations. Perceived benefits also show a positive and significant effect, with a stronger influence compared to accessibility, indicating that SMEs that recognize the advantages of QRIS tend to achieve better financial outcomes. Simultaneously, both variables significantly affect financial performance, with a coefficient of determination (R²) of 0.460, meaning that 46% of financial performance variation is explained by the model. This study contributes to the literature on digital financial inclusion and SME performance by providing empirical evidence from the culinary sector. The findings highlight the importance of improving both accessibility and awareness of QRIS benefits to support sustainable SME growth and competitiveness in the digital economy.